Accommodation Decision Making for Postsecondary Students With Learning Disabilities: Individually Tailored or One Size Fits All?. (September 2016) - Weis, Robert; Dean, Emily L.; Osborne, Karen J.
Clinicians uniformly recommend accommodations for college students with learning disabilities; however, we know very little about which accommodations they select and the validity of their recommendations. We examined the assessment documentation of a large sample of community college students receiving academic accommodations for learning disabilities to determine (a) which accommodations their clinicians recommended and (b) whether clinicians' recommendations were supported by objective data gathered during the assessment process. In addition to test and instructional accommodations, many clinicians recommended that students with learning disabilities should have different educational expectations, standards, and methods of evaluation (i.e., grading) than their nondisabled classmates. Many of their recommendations for accommodations were not supported by objective evidence from students' history, diagnosis, test data, and current functioning. Furthermore, clinicians often recommended accommodations that were not specific to the student's diagnosis or area of disability. Our findings highlight the need for individually selected accommodations matched to students' needs and academic contexts.